2016
DOI: 10.1080/17470218.2015.1093007
|View full text |Cite
|
Sign up to set email alerts
|

Executive control in spoken noun-phrase production: Contributions of updating, inhibiting, and shifting

Abstract: The present study examined how the updating, inhibiting, and shifting abilities underlying executive control influence spoken noun-phrase production. Previous studies provided evidence that updating and inhibiting, but not shifting, influence picture-naming response time (RT). However, little is known about the role of executive control in more complex forms of language production like generating phrases. We assessed noun-phrase production using picture description and a picture-word interference procedure. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 58 publications
3
47
0
1
Order By: Relevance
“…Language ability and the development of EF are related (e.g., Kronenberger, Colson et al, 2014;Sikora, Roelofs, Hermans, & Knoors, 2016;Vygotsky, 1978), although it is difficult to ascertain whether there is only one direction of causality between them or (more likely) whether they are constantly interacting and cumulative in development. In any case, both language and EF are related to children's learning of social and cultural values and the extent to which they are acquired early on, through parent-child interaction, through later peer interaction, and in particular settings (e.g., classroom, public places, and workplace).…”
Section: Discussionmentioning
confidence: 99%
“…Language ability and the development of EF are related (e.g., Kronenberger, Colson et al, 2014;Sikora, Roelofs, Hermans, & Knoors, 2016;Vygotsky, 1978), although it is difficult to ascertain whether there is only one direction of causality between them or (more likely) whether they are constantly interacting and cumulative in development. In any case, both language and EF are related to children's learning of social and cultural values and the extent to which they are acquired early on, through parent-child interaction, through later peer interaction, and in particular settings (e.g., classroom, public places, and workplace).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of language production, the shifting ability plays a role, for example, in switching between planning one utterance to planning another utterance (Sikora et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Sikora et al . () observed that all three components of executive control correlated with the speed of more complex language production by adults, namely noun–phrase production. We discuss this study and its design in some detail because we used the same design in the present study on children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, asymmetrical switch costs were obtained for switching between more complex nondiscrete tasks, in particular, for switching between types of noun phrases in spoken picture description Sikora, Roelofs, Hermans, & Knoors, 2016). Participants switched between short and long phrases (e.g.…”
mentioning
confidence: 99%